Rancang Bangun dan Pengujian Prototype Hybrid Solar Dryer - Jamaldi, Agus; Budi Raharjo, Emanuel; Surwono, Edi; Yordan Santoso, Lewi; Catur Prasojo, Ryan (Universitas Trunojoyo Madura, 2024)
This study aims to test the prototype solar dryer using a hybrid drying mechanism. The study utilized direct and indirect drying models. The indirect drying used solar collectors. Solar collector serves to absorb heat captured by the black body inside. The solar collector media used are flat plates and corrugated plates. The hot air from the solar collector is blown and forced by the blower into the drying chamber. Blowers operate using electrical energy generated by solar panels. The experiment lasted for two days from 09.00 a.m. to 03.00 p.m. The observations focused on the temperature of the solar collector and the drying chamber as well as the output of electricity generated by the solar panels. The test results showed the highest temperature reached by the solar collector with a corrugated plate was 50.500C, while the flat plate was 49.600C. Furthermore, the highest electrical power produced by solar panel was 11.33 Watts.